Is the public convinced that “nothing works?”: predictors of treatment support for sex offenders among Americans - Mancini, Christina (Crime & delinquency, 2016)
It is presumed that public opposition to sex offender treatment derives from the “nothing works” philosophy. However, few studies have systematically unpacked perceptions about sex offender treatment. Drawing on national poll data, this study uses multinomial logistic regression to identify predictors of treatment views. Results indicate that misperceptions about sex crimes, particularly the belief in “stranger danger” and offense amplification, reduce support for treatment. Parents with children under age 17 were less likely to approve of treatment efforts, because they did not believe the treatment research. Separately, belief in high sex offender recidivism was associated with a greater likelihood of not sure responses about treatment. In contrast, desiring more information about how to prevent sexual offending increased support for interventions. Implications are discussed.